2019
DOI: 10.3382/ps/pez354
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of early B-cell development in the chicken embryo

Abstract: The chicken bursa of Fabricius is a primary lymphoid tissue important for B-cell development. Our long-term goal is to understand the role of bursal microenvironment in an early B-cell differentiation event initiating repertoire development through immunoglobulin gene conversion in the chick embryo. We hypothesize that early bursal B-cell differentiation is guided by signals through cytokine receptors. Our theory is based on previous evidence for expression of the receptor tyrosine kinase superfamily members a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…This result is consistent with the previous report that Mel1a response is Gi-dependent in NS-1 cells [42], Chinese hamster ovary cells [43], and human embryonic kidney cells [44]. Over the years, the AKT/GSK-3β/β-catenin signaling is essential for B-cell survival and development in the bursa [45]. In our study, we found that G→B and B→G signi cantly promoted AKT, GSK-3β and β-catenin phosphorylation compared with WW, RR, GG, BB, and R→B.…”
Section: Role Of Melatonin Receptors In Melatonin-mediated a Combinatsupporting
confidence: 93%
“…This result is consistent with the previous report that Mel1a response is Gi-dependent in NS-1 cells [42], Chinese hamster ovary cells [43], and human embryonic kidney cells [44]. Over the years, the AKT/GSK-3β/β-catenin signaling is essential for B-cell survival and development in the bursa [45]. In our study, we found that G→B and B→G signi cantly promoted AKT, GSK-3β and β-catenin phosphorylation compared with WW, RR, GG, BB, and R→B.…”
Section: Role Of Melatonin Receptors In Melatonin-mediated a Combinatsupporting
confidence: 93%
“…This result is consistent with the previous report that Mel1a response is Gi-dependent in NS-1 cells [ 46 ], Chinese hamster ovary cells [ 47 ], and human embryonic kidney cells [ 48 ]. Over the years, AKT/GSK-3 β / β -catenin signaling is essential for B cell survival and development in the bursa [ 49 ]. In our study, we found that G→B and B→G significantly promoted AKT, GSK-3 β , and β -catenin phosphorylation compared with WW, RR, GG, BB, and R→B.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed the expression of the CXCR4 chemokine receptor on the surface of the migrating B cells. The CXCR4 presence has been previously analyzed in the embryonic spleen and bursa (18,21). An increase of the CXCR4 expression was observed in the bursa during the colonization period (26).…”
Section: Discussionmentioning
confidence: 99%
“…The same chemokine receptor and ligand have been shown to be key players in many other migration processes, including the mobilization of mammalian hematopoietic stem cells, lymphocytes (14)(15)(16) but also primordial germ cells (17). CXCR4 and its ligand CXCL12 are both expressed in chickens during B cell development (18)(19)(20)(21). It has been suggested that immature B cells might also migrate toward the bursa under the influence of the CXCR4/CXCL12 interaction.…”
Section: Introductionmentioning
confidence: 99%